The effects of global risk indicators on the MSCI Emerging Markets Index - Selma Öner (Financial Internet Quarterly, 2022)
The rising uncertainty in financial markets in the last 40 years has led to the creation of new financial indices that will enable these uncertainties to be defined and measured. For this purpose, the first volatility index created was the VIX Index as an indicator of uncertainty in the stock markets, which was followed by the OVX Index as an indicator of uncertainty in the oil markets and the GVZ Index as an indicator of uncertainty in the gold markets. These volatility indices are also called "global risk indicators". The MSCI (Morgan Stanley Capital International) Emerging Markets Index, which is the dependent variable of the study, is an index that is frequently followed by fund and portfolio managers in international markets and used as a benchmark. Therefore, in this study, the relationship between the MSCI EM Index and the global risk indicators for the period 28.03.2011-25.03.2022 was examined by the Toda-Yamamoto Causality Test. Afterwards, impulse-response and variance decomposition tests were applied to the variables. As a result of the study, causality relationships from global risk indicators to the MSCI EM Index were determined.
Keywords: C58; F30; F37; 330; MSCI Emerging Markets Index; global risk indicators; VIX Index; OVX Index; GVZ Index; Toda-Yamamoto Causality Test